Parent and Young Adolescent Connection Speaking Heart-to-Heart - Evelyn Rooks-Weir; Alden Hilliker (EDIS)
The purpose of the Parent And Young Adolescent Connection, Speaking Heart-To-Heart curriculum is to enhance the qualities of strong families among those families with at least one member in the ten-through-fourteen age range.